Analisis pengaruh kinerja keuangan daerah terhadap belanja daerah pada Kabupaten/Kota di Provinsi Jambi - Auliani, Desvira; Achmad, Erni; Parmadi, Parmadi (e-Journal Perdagangan Industri dan Moneter, 2024)
The aim of this research is to assess the extent of regional financial performance and how it influences regional spending in districts/cities in Jambi Province. Using secondary data in the form of a time series from 2016 to 2022. The Panel Data Regression Method is the analysis technique used in this research. Calculations using the Degree of Fiscal Decentralization Ratio, Financial Independence Ratio and PAD Effectiveness are used to test the impact on Regional Expenditures and analyze the level of Regional Financial Performance. The results obtained in this research are that the level of regional financial performance and the level of regional financial independence in the Districts and Cities of Jambi Province are in the very low category while the effectiveness of PAD is in the effective category. The estimation results obtained by the Fiscal Decentralization Ratio variable have no effect on regional spending with Prob. 0.4791 and the Regional Financial Independence Ratio has no effect on regional spending with Prob. 0.6869 Meanwhile, the estimated PAD Effectiveness variable has a significant negative effect on regional spending with Prob. 0.0448.